Factors influencing green purchase intention among working consumers in Petaling Jaya, Selangor / Hanisah Mahmud Hishamuddin - Mahmud Hishamuddin, Hanisah (Faculty of Business and Management, 2019)
With the significant increase of seriousness of global warming, people are getting more attention of protecting and preserving the natural environment. The environmental attitude and environmental knowledge of consumers towards the environment is increasing rapidly. This may influence consumer purchase intention to a greener perspective. Thus, it is important to investigate the factor affecting the green purchase intention of consumers. For this study, the aim is to identify the factors influencing green purchase intention among working consumers in Petaling Jaya, Selangor. This research focuses on two objectives which are to determine the relationship between environmental attitude and environmental knowledge towards green purchase intention among working consumers in Petaling Jaya, Selangor and also to identify the most influence factors affecting the green purchase intention among working consumers in Petaling Jaya, Selangor. The sample size of this research is 100 respondents and the appropriate type of investigation for this study is correlation with minimal interference. Quota sampling is used which represent 67 Malay, 19 Chinese, 13 Indian and 1 other which is Iban to ensure that this research will not leave out any of the group. Besides, the questionnaires distribute used Likert-scale to help in collecting the data from the respondents. The results show that environmental attitude is positive, strong and significant relationship towards green purchase intention among working consumers in Petaling Jaya, Selangor. However, the other independent variable which is environmental knowledge is positive, moderate and not significant towards green purchase intention among working consumers in Petaling Jaya, Selangor. Last but not least, the most influence factor affecting the green purchase intention among working consumers in Petaling Jaya, Selangor is environmental attitude with the value of (β = 0.501).